2018
DOI: 10.1177/2055207618775192
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions in digital health engagement: An activity tracker’s ambiguous influence on vulnerable young adults’ engagement in own health

Abstract: ObjectiveActivity trackers are designed to support individuals in monitoring and increasing their physical activity. The use of activity trackers among individuals diagnosed with depression and anxiety has not yet been examined. This pilot study investigates how this target group engages with an activity tracker during a 10-week health intervention aimed to increase their physical activity level and improve their physical and mental health.MethodsTwo groups of 11 young adults (aged 18–29 years) diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…This study is one of only a few to explore these qualitatively. A previous study of activity tracker use in young adults with depression and anxiety reported feelings of guilt and increased anxiety (57). Another qualitative study found evidence of 'unhealthy preoccupation' and 'obsession'…”
Section: Discussionmentioning
confidence: 93%
“…This study is one of only a few to explore these qualitatively. A previous study of activity tracker use in young adults with depression and anxiety reported feelings of guilt and increased anxiety (57). Another qualitative study found evidence of 'unhealthy preoccupation' and 'obsession'…”
Section: Discussionmentioning
confidence: 93%
“…This study is one of only a few to explore these qualitatively. A previous study of activity tracker use in young adults with depression and anxiety reported feelings of guilt and increased anxiety (44). Another qualitative study found evidence of 'unhealthy preoccupation' and 'obsession' relating to health and tness app use in college students (45).…”
Section: Discussionmentioning
confidence: 94%
“…This study is one of only a few to explore these qualitatively. A previous study of activity tracker use in young adults with depression and anxiety reported feelings of guilt and increased anxiety (57). Another qualitative study found evidence of 'unhealthy preoccupation' and 'obsession' relating to health and tness app use in college students (58).…”
Section: Discussionmentioning
confidence: 94%